After Upper Secondary School: Young Adults with Intellectual Disability not Involved in Employment, Education or Daily Activity in Sweden - Renee Luthra; Sara Högdin; Niklas Westberg; Magnus Tideman (Scandinavian Journal of Disability Research, 2018)
There is limited knowledge about young persons with intellectual disability who are Not in Employment, Education or Daily activity (NEED) in Sweden. The aim of the study was to explore the post-upper secondary school situation for persons with intellectual disability not involved in traditional occupations. A national database containing 2955 persons, representing 24.1% of the total (N = 12,269) was used. The results revealed a heterogeneous group where financial support was common and few made use of disability services. Gender, municipality, programme type, financial support and disability services were significantly associated with not having an occupation as opposed to being in employment, education or daily activity. Time was a central factor, as the early years after upper secondary school appear to be an important period for changing NEED status. This is the first large scale study to describe these persons not involved in traditional occupations in Sweden and further research is required.